Madu Bayu” Pudding (Honey Spinach for Mothers) to Treat Anemia in Pregnant Women - Anni Suciawati; Ponisem; Euis Karwati; Ria Fitri Yani; Yhona Farty Indra Yani; Desi Nurabani Sari Sandi; Siti Suci Rahayu; Hani, Umu (Rajaki of Tulip Medika Publisher, 2025)
Based on a preliminary survey on maternal and child health in Cibunar Village taken from the health center report, the number of pregnant women was 124 pregnant women, with 13 pregnant women (11%) experiencing anemia. One alternative that can help increase hemoglobin levels is consuming